2010
DOI: 10.1007/s11270-010-0624-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Temporal Trends of Polycyclic Aromatic Hydrocarbons (PAHs) in Sediments from Lake Maryut, Alexandria, Egypt

Abstract: Surface and core sediments from Lake Maryut, Egypt, one of the most polluted lakes in Egypt, were analyzed for polycyclic aromatic hydrocarbons (PAHs) using gas chromatography-mass spectrometry. This investigation represents the first extensive study of the distribution and sources of PAHs in sediments from Lake Maryut. The total PAHs concentrations (sum of 39 PAH compounds) in surface sediments varied greatly depending on the sampling location and ranged from 106 to 57,800 ng/g dry weight with a mean concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 60 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…Previous studies (Barakat et al 2011;Keshavarzifard et al 2014;Tobiszewski and Namieśnik 2012) suggested that molecular diagnostic ratios of specific PAHs could be used as independent indicators to identify a more specific origin of PAHs compounds in the environment, because the ratios change with the change in composition and burning temperature of organic matter (Meyers and Ishiwatari 1993). Here we calculated and used the ratios of BaP/(BaP + Chr) versus Fluo /( Fluo + Pyr) (Fig.…”
Section: Age Of the Sediment Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Barakat et al 2011;Keshavarzifard et al 2014;Tobiszewski and Namieśnik 2012) suggested that molecular diagnostic ratios of specific PAHs could be used as independent indicators to identify a more specific origin of PAHs compounds in the environment, because the ratios change with the change in composition and burning temperature of organic matter (Meyers and Ishiwatari 1993). Here we calculated and used the ratios of BaP/(BaP + Chr) versus Fluo /( Fluo + Pyr) (Fig.…”
Section: Age Of the Sediment Layersmentioning
confidence: 99%
“…5A) and Ip/(Ip + BghiP) versus Fluo /(Fluo + Pyr) (Fig. 5B) respectively, in order to provide more information about the source appointment of the sediment PAHs at the site (Barakat et al 2011).…”
Section: Age Of the Sediment Layersmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are persistent organic pollutants that contain 2-8 aromatic rings in linear, angular, or cluster arrangements [1]. Due to their toxicity and carcinogenicity, PAHs have attracted the attention of environmental chemists and regulatory agencies for several decades [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Most PAHs corresponded to the development of industrialization and urbanization. Thus, the profile distribution of PAHs in the sediments could elucidate the relationship between the historical trends of PAHs pollution and the socioeconomic development [42][43][44][45]. Many studies have focused on the temporal trends of PAHs in the sediments [16,46].…”
Section: Introductionmentioning
confidence: 99%